QUANTITATIVE DISTRIBUTION PATTERNS AND BIOMAGNETOSTRATIGRAPHY OF MIDDLE AND LATE MIOCENE CALCAREOUS NANNOFOSSILS FROM EQUATORIAL INDIAN AND PACIFIC OCEANS (LEGS 115, 130 AND 138). - RAFFI I.; D'ATRI A.; ROCCHETTI S.; RIO, DOMENICO; FORNACIARI, ELIANA (Ocean Drilling Program:1000 Discovery Drive:College Station, TX 77845:(409)845-2016, EMAIL: distribution@odp.tamu.edu, jennifer--rumford@odp.tamu.edu, INTERNET: http://www-odp.tamu.edu/publications/, Fax: (409)845-4857, 1995)
Selected calcareous nannofossils were investigated by means of quantitative methods in middle and upper Miocene sediments from the tropical Indian Ocean (ODP Leg 115) and equatorial Pacific Ocean (DSDPLeg 85, ODP Legs 130 and 138). Our goal was to test the reliability of the classic biohorizons used in the standard zonations of Martini (1971) and Bukry (1973) and, possibly, to improve biostratigraphic resolution in the Miocene. In a time interval of about 8 m.y., from the last occurrence (LO) of S. heteromorphus ( 13.6 Ma) to the LO of D. quinqueramus ( 5.5 Ma), a total 37 events were investigated, using both the conventional and some additional markers proposed in the literature. At least 17 of these events proved to be distinct biostratigraphic correlation lines between the two considered areas. This integrated biostratigraphic framework increases the biostratigraphic resolution in the middle-upper Miocene interval (of the order of about 0.5 m.y). All the investigated events were tied to the geomagnetic polarity time scale (GPTS) and compared to biomagnetostratigraphy from mid-latitude North Atlantic Site 94-608 (Olafsson, 1991; Gartner, 1992), thus obtaining further information about the biostratigraphic and biochronologic reliability of the investigated events and a significant improvement of the available nannofossil biomagnetostratigraphic model for the middle and late Miocene.